Fine Lines: Mātauranga Māori and Science Classrooms - Stewart, Georgina Tuari; Birdsall, Sally; Tedoldi, Angelo (Springer Science and Business Media LLC, 2026)
Science teachers in Aotearoa New Zealand are under pressure to incorporate mātauranga Māori in their classrooms, yet most know little about it and there is dissent about its place in science education. If mātauranga Māori is not science, then why should science teachers teach it? What does the principle of ‘mana ōrite mō te mātauranga Māori’ mean in science teaching? In this article, three science educators of varying experiences and backgrounds join forces to reflect, separately and together, on the challenges raised by the question of including mātauranga Māori in science classrooms. Using the increasingly popular method of self-study in science education research, most of the length of this article consists of three named sections from each co-author. This article is not designed for beginning readers of the debates about Māori knowledge in science education, which are longstanding and intransigent, and familiarity with the background and relevant literature will be assumed. The aim of the article is not to come up with the ‘right’ answer but to reflect on our learning journeys, inspired by the question of including mātauranga Māori in science education.
Keywords: 3901 Curriculum and Pedagogy; 3903 Education Systems; 39 Education; 13 Education; Education; Cultural responsiveness; Knowledge systems; Mātauranga Māori; Nature of science; Science education